Cognitive Dissonance Bias, Overconfidence Bias dan Herding Bias dalam Pengambilan Keputusan Investasi Saham - Yehezkiel Chris Setiawan; Apriani Dorkas Rambu Atahau; Robiyanto Robiyanto (AFRE (Accounting and Financial Review), 2018)
In practice, there are some aspects which contribute to the decision making process. One of those aspects is the psychological aspect which cannot be separated from human being. The psychological aspect of the study of finance is called the study of behavioural finance (cognitive bias, emotional bias, and social bias) could lead to investor’s irrationality in decision making. This study aimed to analyze the influence of dissonance bias, overconfidence bias, and herding bias on investment decision in Investor Club of Satya Wacana Christian University (SWCU). This study utilizes the purposive sampling method. The sample in this study covers the whole investor in Investor Club of SWCU. The results of this study indicate that: (i) Cognitive dissonance bias has an insignificant influence to investment decision ; (ii) Overconfidence bias has a positive and significant influence to investment decision; (iii) Herding bias has an insignificant influence to the investment decision. This means that investors tend to use the emotional aspect rather than on the cognitive and social aspects of investment decision making. As a result, investors are overconfident of their ability and the outcome of investment decisions is not maximal and can cause losses. DOI: https://doi.org/10.26905/afr.v1i1.1745